The impact of online payments on employee benefits - Raposo, Margarida Isabel Ministro (2020)
Employee Benefits have been earning increasing relevance as a Human Resource Management practice. The present research discusses the importance of the topic from employees’ perspective, in order to theoretically and practically contribute to debate on this field. Furthermore, acknowledging that many of employee benefits are used as a payment method, it has been also relevant to consider means of payment evolution, and its possible impact on Employee Benefits. On regards to theory, the importance of employee benefits, the relevance of the format for its distribution and the most valued employee benefits are discussed. Concerning practical implications, employees’ intention to adopt online forms of payment for the use of Employee Benefits is explored – particularly for the use of Education Employee Benefits. Moreover, this in-company project explores and defines the most adequate service-mix, from all stakeholders’ perspectives. The most relevant conclusions from this research highlight the high value employees attribute to Employee Benefits, particularly to those related to education and childcare. Also, it is clear a preference for online forms of payment for its distribution and use, from all stakeholders’ perspective. Furthermore, employees reveal a clear intention to adopt online forms of payment for the use of Education Employee Benefits. The research is limited to Portuguese context, conditioning extrapolations for other geographies, considering the specific legal context underlying Employee Benefits topic. This project was developed in partnership with Edenred Portugal.